Temporary spinal cord stimulation combined with lidocaine patch for postherpetic neuralgia in the elderly: a controlled study - Yun Li; Chunhui Hao; Shengtao Wang; Feng Qiu; Xuli Zhao; Tao Sun (Frontiers in Neurology)
BackgroundPostherpetic neuralgia (PHN) is a chronic neuropathic pain condition in elderly patients following herpes zoster infection. Conventional treatments often have inconsistent efficacy and significant side effects. Combining spinal cord stimulation (SCS) with lidocaine patches may enhance pain relief by targeting central and peripheral pain mechanisms.MethodsThis randomized, controlled, single-blind trial enrolled 97 patients aged ≥60 years with PHN lasting ≥6 months. Participants were assigned to SCS with a 5% lidocaine patch (n = 49) or SCS with a placebo patch (n = 48). Both groups received oral pregabalin. The placebo patch was identical in appearance to ensure blinding. Pain intensity (VAS) and sleep quality (PSQI) were assessed at baseline and on days 1, 3, 7, 30, and 90 post-interventions. Subgroup analyses by age and PHN duration were conducted.ResultsAt day 90, the experimental group had greater reductions in VAS scores (1.6 ± 1.1) than the control group (2.7 ± 1.3, p < 0.01). Clinically significant pain relief (≥50% VAS reduction) was achieved by 72.3% in the experimental group versus 45.8% in the control group (p = 0.038). PSQI scores improved more in the experimental group (5.3 ± 2.1) than in the control group (8.2 ± 2.7, p = 0.021). Patients with PHN duration <60 days benefited more from combination therapy. Adverse events were minimal and similar between groups.ConclusionCombining SCS with lidocaine patches significantly enhances pain relief and sleep quality in elderly PHN patients compared to SCS alone. Further multicenter studies are recommended to validate these findings and assess long-term outcomes.Clinical trial registrationhttps://www.chictr.org.cn/searchprojEN.html, ChiCTR2000039059.